Correlation analysis of serum FGF9, Sestrin 2 and HBDH with the severity of sepsis: Serum FGF9, Sestrin 2 and HBDH with the severity of sepsis - He, Jian; Lin, Xinru; Ding, Xiang; Liu, Maoxia (Journal of Medical Biochemistry, 2025)
Objective: To explore the correlation between serum fibroblast growth factor 9(FGF9), Sestrin2 and hydroxybutyrate dehydrogenase (HBDH) and the severity of sepsis, and to analyze the predictive value of FGF9, Sestrin2 and HBDH for clinical outcome.Methods: A retrospective examination of 125 patients with sepsis admitted to our institution between May 2022 and May 2025 was carried out. According to the severity of the disease, There were 50 cases in the septic shock group and 75 cases in the sepsis group. According to the clinical outcomes of the patients, they were divided into a death group of 103 cases and a survival group of 22 cases. Observe the levels of serum FGF9, Sestrin2 and HBDH in each group. Analysis of the relationships between FGF9, Sestrin2, HBDH, and the severity of sepsis was done using the Spearman correlation coefficient model. Using multivariate logistic regression analysis, the factors influencing the prognosis of patients with sepsis were investigated.  FGF9, Sestrin2, and HBDH were evaluated for their prognostic usefulness for the prognosis of sepsis patients using the receiver operating characteristic (ROC) curve.Results: Compared with the sepsis group, The level of FGF9 in the septic shock group was lower [(122.41±21.45) pg/mL vs (145.36±23.68) pg/mL], while the levels of Sestrin2 and HBDH were both higher [(15.75±2.34) ng/mL] vs (8.36 + 0.93) ng/mL, (232.14-34.77) U/L vs (166.25 + 24.85) U/L], the differences were statistically significant (P
Keywords: Sepsis; Fibroblast growth factor 9; Sestrin2; Hydroxybutyrate dehydrogenase; Correlation analysis